Local Buckling Development of H-Section Steel Core of Buckling-Restrained Brace - Wei Li; Jing Dong; Hui Qu; Lanqin Wang; Kun Zhao (Buildings, 2022)
To enhance the theoretical basis for the half-wavelength evaluation of high-order local buckling of section steel used as inner core of buckling-restrained brace, this paper conducts theoretical and numerical studies on the local buckling development of an H-section steel core of buckling restrained brace. Firstly, the elastic buckling development of the flange under monotonic compression is theoretically discussed based on the elastic buckling theory of plate and the principle of virtual displacement. The numerical model for the buckling restrained brace with H-section steel core is then established based on Abaqus, and the elastic buckling development of the flange is validated. Finally, further numerical studies are conducted to reveal the elasto-plastic buckling development of the flange and web under cyclic loading. It is found that the local buckling development of the flange and web of the H-section steel core are different from that of the flat plate core of buckling restrained brace. Under cyclic loading, the shortest buckling wave of the flange and web are induced by the buckling of plates on the two sides of the contact point near the ends. It is confirmed that there is no need to consider the lateral support from the restraining members to evaluate the minimum half-wavelength of high-order local buckling for section steel core of buckling-restrained brace.